Paradigma Kepemimpinan Transformatif Menuju Madrasah Unggulan - Indah Nurrohmah; Fitri Wulandari (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2021)
The concept of leadership is still developing from time to time. Leadership theory also continues to evolve to find the most effective form of leadership in organizational management. In the 1980s, transformative leadership was born and is often referred to as an effective leadership model. In its preparation, this leadership concept uses a leader-follower perspective. Transformative leadership is claimed to be the most effective leadership pattern, which can achieve the main goals. Using a descriptive qualitative approach with library research methods, and analyzed using the theory of "paradigm" by Thomas Kuhn. This research is basically to reveal: 1. What is the transformative leadership paradigm? 2. How is the application of transformative leadership in Madrasah Ibtidaiyah? This study aimed to analyze the transformative leadership paradigm using the theory of Thomas Kuhn and initiating the application of transformative leadership in Madrasah Ibtidaiyah and resulting in the following conclusions: 1. Transformative leadership paradigm in terms of exemplar aspects, subject matter, theory, and method. 2. Madrasah Ibtidaiyah, which uses a transformative leadership management paradigm, always develops idealized influence, inspirational motivation, intellectual stimulation, and individual consideration. Transformative leadership is very relevant to be applied in Madrasah Ibtidaiyah to create Effective and Excellent Madrasahs.